Longitudinal Family Business Research – Review of the Literature - Judit Csákné Filep; László Radácsi (European Management Studies)
Purpose: Cross-sectional research methods are not able to grasp the special characteristics and unique operation modes of family businesses. The aim of the study is to map the type of topics examined and methodologies used in longitudinal empirical studies in family business research. The study examines the topics and methodologies covered in the literature and the advantages and challenges of each methodological approach. Design/methodology/approach: We conducted a literature review and drew conclusions based on a detailed analysis of 99 articles. The paper presents the distribution of topics, the applied methodology, and evaluates quantitative and qualitative methods. Findings: Within seven topics identified, most studies were published on family business governance, operation, succession, and the internationalization of family firms. The majority of longitudinal family business research is based on quantitative methodologies, but the proportion of studies using qualitative approaches is also gaining momentum, while the use of mixed-method approaches is negligible. Limitations: We collected the data from the Web of Science database and our study may reflect the limitations of this database. Two of our researchers conducted the article selection process manually and, despite the greatest care, it is possible that valuable articles were left out of the analysis. Due to the applied selection and analysis methods, the comparability of our results with more comprehensive literature reviews on family businesses is limited. The results relate to longitudinal, empirical research papers only. The time span covered by our research is narrow, there are more comprehensive and up-to-date literature reviews available. The study contributes to longitudinal family business research